Human philosophy in sufism - Namоzov Babir Bahrievich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
In this article the human philosophy of the theoretician of naqshbandiyya schooling Khoja Mukhammad Porso is scrutinized. His ideas on its enrichment with the new ideas, the role and responsibility of human in the universe are widely illuminated. The translations and citations from the sources in Arabic and Persian are given by the author.